Evaluating the Reality of University Sports from the Point of Players View in Iraqi Universities - Hassanine Juma Assery (Journal of Global Pharma Technology, 2016)
The current study objectives at following:To identify the reality of sports university from the perspective of players of Iraqi universities.Evaluation of the reality of university sports from the perspective of players of Iraqi universities.The researchers used the descriptive method in the survey method. The research community identified the 156 Iraqi players in the Iraqi universities and then selected a sample of 70 randomly selected players. The researchers then selected and applied the measure of the reality of university sports on the research sample. Results and the use of appropriate statistical treatments to reach the results after the results were presented analyzed and discussed the researchers reached the most important conclusions of the following:Ability of the measure of the reality of Sports University, which researchers applied in measuring the reality of university sports in Iraqi universities.The reality of university sports in Iraqi universities is at the acceptable level.There is weakness in the reality of university sports in Iraqi universities.Keywords: Evaluating, University sports and Iraqi Universities.